Coronary perivascular epicardial adipose tissue and major adverse cardiovascular events after ST segment-elevation myocardial infarction. (June 2020) - Toya, Takumi; Corban, Michel T.; Imamura, Kimitake; Bois, John P.; Gulati, Rajiv; Oh, Jae K.; Lerman, Lilach O.; Lerman, Amir
Abstract: Background and aims: Perivascular epicardial adipose tissue (pEAT) plays a key role in the progression of atherosclerosis, plaque rupture, and thrombosis. However, the relationship between pEAT and prognosis after revascularization of ST-segment elevation myocardial infarction (STEMI) is unknown. This study aimed to investigate the relationship between pEAT thickness and prognosis after STEMI. Methods: We studied 180 STEMI patients (mean age 59.4 ± 13.3 years, 78.9% male) who underwent cardiac magnetic resonance (CMR) imaging within 1 week of prompt infarct-related artery revascularization and 52 age/sex/body mass index-matched controls (mean age 59.9 ± 13.5 years, 78.9% male). pEAT thickness indexed to body surface area at five locations, infarct size, left ventricular ejection fraction (LVEF), and coronary microvascular obstruction (MVO) were evaluated by CMR. Associations between pEAT index and 1-year composite major adverse cardiovascular events (MACE), infarct size, LVEF, and MVO were analyzed. Results: Mean pEAT indices were significantly higher in STEMI patients than controls. In STEMI patients, higher pEAT indices at the superior and inferior interventricular groove (SIVG and IIVG, respectively) were significantly associated with larger infarct size, higher prevalence of MVO, and inversely correlated with post-infarct LVEF. SIVG pEAT index was an independent predictor of composite MACE in post-STEMI patients with an odds ratio of 2.26 (95% confidence interval 1.63–3.13; p  < 0.0001) after adjustment for age, sex, LVEF, and 2.71 (95% confidence interval 1.93–3.80; p  < 0.0001) after adjustment for age, sex, previous myocardial infarction, diabetes mellitus, and renal function. Conclusions: STEMI patients have significantly higher pEAT indices than controls. SIVG pEAT index independently predicts composite MACE in revascularized STEMI patients, underscoring the potentially prognostic value of this variable. Graphical abstract: Image 1 Highlights: Perivascular epicardial adipose tissue (pEAT) is thicker in ST-segment elevation myocardial infarction (STEMI) patients than controls. pEAT is thicker in patients with major adverse cardiovascular events (MACE) than patients without MACE following STEMI. pEAT at interventricular groove was associated with larger infarcts and coronary microvascular obstruction (MVO). pEAT at interventricular groove was inversely correlated with left ventricular ejection fraction (LVEF). pEAT thickness affects prognosis after STEMI.